2013
DOI: 10.4028/www.scientific.net/amr.774-776.279
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steady State Moisture Diffusion Flow in Homogenous Pineapple Leaves Particleboard

Abstract: Non steady state diffusion flow is unstable movement of moisture in a material which changes with respect to time. Diffusion coefficient describes the rate at which water moves from the interior to the surface of the materials. Absorption and desorption are the variables that are used to determine the diffusion coefficient. Understanding of the water absorption and desorption is important since it affects the mechanical properties of materials such as strength and durability properties. Water absorption and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Brake pad samples with high resin mixtures should have higher density and strength but we found that in lower BD samples this could be due to low-density composites having more voids, porosities, and spaces within the composite's components. However, we need to do further research to confirm this result, and it will be done in our future research [42]. The DA samples had the highest density, which was due to the closer packing of the BD particles, which created more homogeneity across the whole-body composite phase.…”
Section: Physical Appearance Of Brake Padsmentioning
confidence: 86%
See 2 more Smart Citations
“…Brake pad samples with high resin mixtures should have higher density and strength but we found that in lower BD samples this could be due to low-density composites having more voids, porosities, and spaces within the composite's components. However, we need to do further research to confirm this result, and it will be done in our future research [42]. The DA samples had the highest density, which was due to the closer packing of the BD particles, which created more homogeneity across the whole-body composite phase.…”
Section: Physical Appearance Of Brake Padsmentioning
confidence: 86%
“…The coefficient of friction (μ) is the ratio of the frictional force (f; Newton) to the applied force (N; Newton), which is expressed in the form of Eq. 3 below [42].…”
Section: Friction Testmentioning
confidence: 99%
See 1 more Smart Citation